Die Rechtsstellung des Generalanwalts am Gerichtshof der Europäischen Union - Brügmann, Jonas (Schriftenreihe Europäisches Recht, Politik und Wirtschaft, 2023)
The Advocate General has a lasting influence on the case law of the European Court of Justice and his opinions are widely publicised both in specialist circles and in the general media. In order to better understand the significance of the Advocate General and his opinions for European law, his legal position is comprehensively analysed in this work. Firstly, the selection of the Advocates General and the relevant public service law are elaborated in order to analyse the rights, duties and functions of the Advocate General, with a particular focus on independence and possible impairments. Finally, potentially relevant reforms are considered.